The Role of Nigella sativa and Its Active Constituents in Learning and Memory - Sahak, M.K.A.; Kabir, N.; Abbas, G.; Draman, S.; Hashim, N.H.; Adli, D.S.H. (Hindawi, 2016)
The loss of the ability for learning and memory is a prominent feature of dementia, which affects millions of individuals all over the world, due to either neurodegenerative diseases or brain injury. Although a lot of information is known about the pathology involved, treatment remains elusive at best. The Black Seed of Nigella sativa has been historically and religiously used for thousands of years for preventing and treating many different kinds of diseases. This review article looks at Nigella sativa and its potential role in facilitating learning and memory. The possible use of this seed’s extract or compounds isolated from it, such as thymoquinone, for treating damaged brain neural tissue is discussed. The evidence presented in this paper appears to be supporting the hypothesis that this plant and/or its bioactive constituents can enhance learning and memory in health and disease in animals and humans.